360-Degree Communication and Professionalism Assessment Instrument - Christopher Weaver (Association of American Medical Colleges, 2006)
Abstract Introduction This resource is an evaluation tool designed to provide an assessment of residents in the professionalism and interpersonal communication skills competencies. Methods The first page is a simple description of the process with instructions. The second is the assessment instrument. An 11-point Likert-type scale is used for each of the seven questions to evaluate the communication and professionalism displayed with patients, families, and staff. The tool also evaluates leadership skills. Results A randomly developed sampling of nurses and support staff complete the assessment instrument for individual residents. Junior residents performing poorly on this evaluation routinely improve a great deal when evaluated as senior residents. Discussion The simplicity of the form has allowed for excellent compliance from the evaluators. Our residents are very responsive to the feedback received from non-physician working colleagues. This assessment from other care-givers in the department early in the residents training allows for an effective remediation process during residency. The instrument utilized is a simple one to enhance compliance by the variety of busy staff from who we seek feedback. The evaluator may state that they had inadequate exposure to evaluate the resident.